Downstreaming Mineral Resources in Indonesia in Bibliometric Analysis - Brigita Purnawati Manohara; Muhammad Iqbal; Hyronimus Rowa; Suhajar Diantoro; Tjahyo Suprajoyo (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Although research has been shrinking over the last few years, despite growing publications, its recent bibliometric structural development remains relatively underexplored regarding Indonesia's continuing industrial policy after the nickel export ban and Mining Law (2020). Objective: To map research development, collaboration networks, and trending topics while also identifying gaps in mineral downstreaming research. Methods: Using Publish or Perish in Google Scholar, 1,000 publications (2005–2025) were obtained and analyzed using VOSviewer for co-authorship and keyword co-occurrence. Results: Publications increased exponentially after 2020, coinciding with Indonesia's nickel export ban. Co-authorship analysis identified 32 connected authors across 8 clusters, with Chinese-affiliated researchers dominating the network (Wang, Zhang, Chen, Li). Keyword co-occurrence mapping revealed 1,083 interconnected items across 26 thematic clusters, with the discourse evolving from resource nationalism and investment policy toward critical minerals, battery ecosystems, ESG, and sustainability. Conclusion: The bibliometric map reveals a maturing but fragmented research landscape, with underexplored areas in green governance, mineral circularity, and domestic social impact. This study contributes the first systematic bibliometric overview of mineral downstreaming research in Indonesia, providing a research roadmap for scholars, policymakers, and industry stakeholders navigating Indonesia's role in the global clean energy supply chain.